Defensive security handbook best practices for securing infrastructure - Berlin, Amanda; Brotherston, Lee; Reyor, William F. (Ascent Audio, 2024)
Despite the increase of high-profile hacks, record-breaking data leaks, and ransomware attacks, many organizations don't have the budget for an information security (InfoSec) program. If you're forced to protect yourself by improvising on the job, this pragmatic guide provides a security-101 handbook with steps, tools, processes, and ideas to help you drive maximum-security improvement at little or no cost. Each chapter in this book provides step-by-step instructions for dealing with issues such as breaches and disasters, compliance, network infrastructure, password management, vulnerability scanning, penetration testing, and more. Network engineers, system administrators, and security professionals will learn how to use frameworks, tools, and techniques to build and improve their cybersecurity programs. This book will help you plan and design incident response, disaster recovery, compliance, and physical security; learn and apply basic penetration testing concepts through purple teaming; conduct vulnerability management using automated processes and tools; and use IDS, IPS, SOC, logging, and monitoring. You'll also bolster Microsoft and Unix systems, network infrastructure, and password management; use segmentation practices and designs to compartmentalize your network; and reduce exploitable errors by developing code securely.
Keywords: Computer networks -- Security measures -- United States; Computer security -- Planning -- United States; Computer security -- Management -- United States; Information technology -- Security measures; Réseaux d'ordinateurs; Sécurité; Mesures; États-Unis; Sécurité informatique; États-Unis; Planification; Sécurité informatique; États-Unis; Gestion; Technologie de l'information; Sécurité; Mesures; Audiobooks; Livres audio